Long-Term Outcomes of Coronary and Carotid Artery Disease Revascularization in the FRIENDS Study - Fabrizio Tomai; Anna Piccoli; Fausto Castriota; Luca Weltert; Bernhard Reimers; Gabriele Pesarini; Raoul Borioni; Giovanni De Persio; Roberto Nerla; Andrea Pacchioni; Alberto Cremonesi; Flavio Ribichini (Journal of Interventional Cardiology)
Objectives. The aim of this study is to assess long-term-outcomes of patients with concomitant CAD and COD treated with different revascularization strategies. Background. Multisite artery disease is common and patients with combined disease have poor prognosis. The best therapeutic strategy for patients with concomitant carotid obstructive disease (COD) and coronary artery disease (CAD) remains controversial. Methods. This observational registry enrolled, between January 2006 and December 2012, 1022 consecutive patients from high volume institutions with concomitant CAD and COD suitable for endovascular, surgical, or hybrid revascularization in both territories selected by consensus of a multidisciplinary team. Results. The cumulative incidence of 5-year major cardiovascular events (MACCE) including cardiovascular death, myocardial infarction (MI), or stroke in the overall population was 12%. The incidence of 5-year MACCE was not statistically different in the surgical, endovascular, or hybrid patients group (10.1% vs. 13.0% vs. 13.2%, P = .257, respectively). However, the hybrid group exhibited rates of myocardial infarction, chronic kidney disease, and cumulative incidence of all clinical events higher than the surgical group. After propensity score matching, the incidence of 5-year MACCE was similar in the three groups (13.0% vs. 15.0% vs. 16.0%, p = .947, respectively). Conclusions. An individualized revascularization approach of patients with combined CAD and COD yields very good results at long-term follow-up, despite the high risk of this multilevel population even when the baseline clinical features are equalized.